Noninvasive Positive Airway Pressure Treatment in Children Less Than 12 Months of Age. (15th June 2016) - Adeleye, Adetayo; Ho, Alice; Nettel-Aguirre, Alberto; Buchhalter, Jeffrey; Kirk, Valerie
Abstract : Study Objectives . We identified the associated conditions of patients less than 12 months of age who were referred for polysomnogram (PSG) studies. We collated PSG findings and physician interpretation. We determined the correlation between the recommended treatment by the PSG interpreting physician and actual prescribed treatment by the referring or subjects' physician. We determined adherence with noninvasive positive airway pressure (PAP) treatment. Methods . This was a retrospective cohort study. Participants included children less than 12 months of age referred for PSG studies between 2007 and 2012. Results . 92 patients under the age of 12 months were included in the study analysis. Mean (standard deviation, SD) age in days at time of the PSG study was 208.5 (101.2). 35 (38%) patients had a diagnosis of Trisomy 21. Seven (8%) patients had no prior diagnosis. Median (Q1, Q3) apnea hypopnea index (AHI) was 22.5 (11.3–37.0). Agreement between the PSG interpreting physician's recommendation and actual prescribed treatment by the referring or subjects' physician was 85.9% [95% CI 77.1–91.6]. Mean (SD) percentage days with PAP therapy usage more than 4 hours was 25.2% (32). Conclusions . In our experience, despite consistent physician messaging to families, adherence with noninvasive PAP treatment is low.